Inventory Management System for FCSIT / Ong Poh Ling - Ong , Poh Ling (2001)
The inventory management system is a client server system with the objective to computerize and enhance the inventory management system for Faculty Computer Science and Information Technology (FCSIT). The server side contains all related basic inventory management rules, documents, and database. Meanwhile the client consists two sections, which are User and Administrator. The User section allows user to browse through the faculty information and search available items. The Administrator section is for the system administrator to perform all administrative tasks namely maintaining the inventory database. The inventory management system for faculty was developed using Microsoft Visual Basic 6.0 to create the application programs, Microsoft Access 97 as the prototype testing, Microsoft SQL Server 7.0 as the database server and Windows NT Server 4.0 as the network operating system. The inventory management system for the faculty is developed with the purpose to enhance the inventory management system for the faculty. Most of the current in entry management applications are developed to suit the requirement of manufacturer and not for the university. Therefore, the proposed system is to customize an inventory management application to suit the inventory control needs of the faculty.